2018
DOI: 10.15171/joddd.2018.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of anesthetic efficacy of warm, buffered and conventional 2% lignocaine for the success of inferior alveolar nerve block (IANB) in mandibular primary molars: A randomized controlled clinical trial

Abstract: Background: Maintaining primary teeth in the oral cavity is of prime importance, and grossly carious teeth may require pulp therapy for the same. Pain on injection and incomplete anesthesia causes failure of the procedure and result in fear and anxiety. Various methods have evolved to overcome this; such as distraction, topical anesthesia, etc. A few techniques regaining popularity in dentistry in recent times is the warming or buffering of the solution prior to administration. This study thus aimed to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 32 publications
2
42
2
1
Order By: Relevance
“…Warming the local anesthetic solution is accomplished with the thermostatic heat bath [10,13], baby bottle warmer [11],…”
Section: Methods Of Warming Anesthetic Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Warming the local anesthetic solution is accomplished with the thermostatic heat bath [10,13], baby bottle warmer [11],…”
Section: Methods Of Warming Anesthetic Solutionsmentioning
confidence: 99%
“…Both infiltrations and blocks were evaluated in the study by Ram et al, 2002 [13]. [11,13], and the other two studies used Wong Baker-FACES Pain Scale (WB-FPS) [9,10]. Only the study by Ram et al, 2002, reported Conclusions: Based on the aforementioned discussion, the following conclusions can be drawn:…”
Section: Type Of Injectionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is the first study to be reported in the literature where conventional and buffered lignocaine as well as articaine have been used as the study groups. Previous study by Kurien et al used warm,buffered and conventional lignocaine as the study groups [27]. Buffered articaine is statistically significantly a better anesthetic agent when compared to conventional or buffered lignocaine (Tables 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 92%
“…Esta propriedade está diretamente ligada com a duração da ação do anestésico e é representada pela porcentagem de fármaco circulante ligada a proteínas e pode correlacionar-se com a afinidade de um anestésico por proteínas dentro dos canais de sódio. Quanto maior a tendência de ligação às proteínas, mais tempo o anestésico sustentará o bloqueio neural (Brunton et al, 2005;Catteral, Mackie, 2006;Malamed, 2013) A lidocaina é o anestésico padrão de comparação nos trabalhos, onde se estuda a eficácia anestésica, tempo de latência e duração de anestésicos (Tortamano et al, 2009, Elbay et al, 2016Visconti et al,2016, Cook et al,2018, Kurien et al, 2018, Ranjan et al, 2018,,Badr , Aps, 2018. É o mais usual anestésico local de uso odontológico, e está sempre associado a um vasoconstritor, geralmente a epinefrina, com concentração usual de 1:100 000 ou 1:200.000 (Tabela.1) (Malamed, 2013).…”
Section: Rnh + > Rn + H +unclassified